2017
DOI: 10.1177/2309499017742740
|View full text |Cite
|
Sign up to set email alerts
|

K-rod dynamic internal fixation versus microendoscopic discectomy for the treatment of single-segment lumbar disc herniation

Abstract: K-rod internal fixation and MED produce satisfactory outcomes in the treatment of single-segment lumbar disc herniation. K-rod internal fixation is superior to MED in preventing adjacent segment degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Furthermore, it can preserve the ROM of the surgically corrected segment, thus reducing the stress load on the adjacent segments and compensating the ROM [20,21]. Other studies have also supported the view that the dynamic stabilization system can reduce ASD [22][23][24]. In this study, the total lumbar ROM of the Isobar TTL group at the last follow-up was significantly greater than that of the rigid group, indicating that Isobar TTL helps retain a certain degree of the total lumbar ROM.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, it can preserve the ROM of the surgically corrected segment, thus reducing the stress load on the adjacent segments and compensating the ROM [20,21]. Other studies have also supported the view that the dynamic stabilization system can reduce ASD [22][23][24]. In this study, the total lumbar ROM of the Isobar TTL group at the last follow-up was significantly greater than that of the rigid group, indicating that Isobar TTL helps retain a certain degree of the total lumbar ROM.…”
Section: Discussionsupporting
confidence: 70%
“…The ROM of the operative segment was also preserved, which reduced stress on the segments, and provided a compensation of the ROM [21,26]. Dynamic K-Rod stabilization delays the occurrence of adjacent-level degeneration [11,13,16]. Due to the relatively short follow-up time of this study, it will take longer and more follow-up to further confirm the reliability of the results.…”
Section: Radiologic Outcomes Of Typical Casementioning
confidence: 81%
“…Thereby, the relevant functional activities could be performed earlier after the operation, which signi cantly shortened the postoperative hospital-stay duration. Recent studies have shown that both the methods can provide bene cial short-term effects (21)(22). On the contrary, spinal fusion is performed for coping with lumbar instability in the PLIF procedure, which can be attributed to some complications such as adjacent segment diseases (ASD) (3,(5)(6), considering that the spinal fusion may change the rotation center over the disc, increasing the stress on the intervertebral disc of the adjacent mobile segments (23).…”
Section: Discussionmentioning
confidence: 99%